Selection for Function: From Chemically Synthesized Prototypes to 3D‐Printed Microdevices. (25th June 2020) - Bachmann, Felix; Giltinan, Joshua; Codutti, Agnese; Klumpp, Stefan; Sitti, Metin; Faivre, Damien
Abstract : Magnetic microswimmers are promising devices for biomedical and environmental applications. Bacterium flagella‐inspired magnetic microhelices with perpendicular magnetizations are currently considered standard for propulsion at low Reynolds numbers because of their well‐understood dynamics and controllability. Deviations from this system have recently emerged: randomly shaped magnetic micropropellers with nonlinear swimming behaviors show promise in sensing, sorting, and directional control. The current progresses in 3D micro/nanoprinting allow the production of arbitrary 3D microstructures, increasing the accessible deterministic design space for complex micropropeller morphologies. Taking advantage of this, a shape is systematically reproduced that was formerly identified while screening randomly shaped propellers. Its nonlinear behavior, which is called frequency‐induced reversal of swimming direction (FIRSD), allows a propeller to swim in opposing directions by only changing the applied rotating field's frequency. However, the identically shaped swimmers do not only display the abovementioned swimming property but also exhibit a variety of swimming behaviors that are shown to arise from differences in their magnetic moment orientations. This underlines not only the role of shape in microswimmer behavior but also the importance of determining magnetic properties of future micropropellers that act as intelligent devices, as single‐shape templates with different magnetic moments can be utilized for different operation modes. Abstract : The special swimming behavior of a magnetic micropropeller selected from a pool of randomly shaped particles is transferred on reproducible devices using recent advances in 3D printing. A single propeller shape with varying magnetic properties shows a wide range of swimming characteristics. This poses new challenges, but also new opportunities for magnetic micropropellers.